Outsider art : art brut and its affinities - Rhodes, Colin (London : Thames & Hudson, 2022)
"Outsider art is work created by self-taught isolates, untrained visionaries, spiritualists, folk artists, psychiatric patients, prisoners, and others beyond the imposed margins of society and the art market. Coined by Roger Cardinal in 1972 as an English equivalent for Jean Dubuffet's category of 'art brut' - literally 'raw art' - and originally regarded as defining a distinctly western phenomenon, the term has come to encompass a wide variety of work produced across the world. In this indispensable guide, substantially revised and updated with greater coverage of global practitioners, Colin Rhodes surveys the history and reception of outsider art, while providing fresh insights into the achievements of both major figures and recently discovered artists. From now canonical and widely celebrated artists including Nek Chand, Aloïse Corbaz, Henry Darger, Madge Gill and Adolf Wölfli, to contemporary practitioners such as Noviadi Angkasapura, Marilena Pelosi and Shinichi Sawada, these individuals passionately and obsessively pursue the pictorial expression of their vision."--Page [4] of cover.
Art Brut and its affinities -- Psychopathological art -- Alternative worlds -- Self-taught visionaries -- Other positions -- The contemporary turn.
First published in 2000 as Outsider art: spontaneous alternatives.
Includes bibliographical references and index.
Keywords: Art brut; Art brut; Outsider art; Outsider art; Illustrated works; Informational works